2023
DOI: 10.3390/ijms241411673
|View full text |Cite
|
Sign up to set email alerts
|

T Cells in Colorectal Cancer: Unravelling the Function of Different T Cell Subsets in the Tumor Microenvironment

Abstract: Therapeutic options for metastatic colorectal cancer (mCRC) are very limited, and the prognosis using combination therapy with a chemotherapeutic drug and a targeted agent, e.g., epidermal growth factor receptor or tyrosine kinase, remains poor. Therefore, mCRC is associated with a poor median overall survival (mOS) of only 25–30 months. Current immunotherapies with checkpoint inhibitor blockade (ICB) have led to a substantial change in the treatment of several cancers, such as melanoma and non-small cell lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 250 publications
(310 reference statements)
0
2
0
Order By: Relevance
“…Among the components of the tumor immune microenvironment, the degrees of CD4 + cell and CD163 + cell infiltration and IL-6 expression in cancer tissues were significantly correlated with FDG PET/CT imaging features of primary tumors. Although CD4 + T cells can polarize into different subsets, which either stimulate or inhibit the immune response to cancer cells, higher levels of CD4 + cell infiltration in tumor tissues were related to better clinical outcomes in colorectal cancer in previous studies [ 10 , 11 , 29 ]. In our study, MTV and TLG showed significant negative correlations with CD4 + cell infiltration and significant positive correlations with tumor grade.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the components of the tumor immune microenvironment, the degrees of CD4 + cell and CD163 + cell infiltration and IL-6 expression in cancer tissues were significantly correlated with FDG PET/CT imaging features of primary tumors. Although CD4 + T cells can polarize into different subsets, which either stimulate or inhibit the immune response to cancer cells, higher levels of CD4 + cell infiltration in tumor tissues were related to better clinical outcomes in colorectal cancer in previous studies [ 10 , 11 , 29 ]. In our study, MTV and TLG showed significant negative correlations with CD4 + cell infiltration and significant positive correlations with tumor grade.…”
Section: Discussionmentioning
confidence: 98%
“…M2 macrophages perform pro-tumoral functions by secreting diverse pro-inflammatory cytokines and enzymes, such as interleukin-6 (IL-6) and matrix metalloproteinase-11 (MMP-11) [ 8 , 9 ]. In contrast, CD4 + and CD8 + T cells play a crucial role in anti-tumor immunity and help change the tumor microenvironment into a more tumor-suppressive condition [ 10 , 11 ]. These diverse cells and components in the tumor immune microenvironment are considered potential treatment targets and prognostic factors for colorectal cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 Dysregulated T cells have been implicated in several intestinal pathologies like colorectal cancer, inflammatory bowel disease and celiac disease. 21 , 22 , 23 Here, T cells isolated with the different digestion enzymes were analyzed using flow cytometry as shown in Figure 5 A. From the live CD45+ total leukocytes, TCR αβ and TCR γδ were used for gating αβ -T cells and γδ -T cells, respectively.…”
Section: Expected Outcomesmentioning
confidence: 99%